Do research and extension services improve small farmers’ perceived performance? - Garcia Alvarez Coque, Jose Maria (2018)
In Europe, research and extension services (RES) play a relevant role in the agricultural sector. A Structural Equation Model has evaluated the impact of RES on perceived farm performance in a sample of 247 holdings. Our interest is not only on the perceived benefits for small-scale holdings which request technical advice but also on the intermediate role of Strategic Orientations (SO), including market orientation and innovation attitude, that could improve the effectiveness of RES. Our key findings support that SO is a dynamic and determinant organizational factor that RES can stimulate, and involve a positive effect on farms’ perceived performance.